2020
DOI: 10.3390/v12090905
|View full text |Cite
|
Sign up to set email alerts
|

Paving the Way to Unveil the Diversity and Evolution of Phage Genomes

Abstract: Phage biology has been developing for the last hundred years, and the potential of phages as tools and treatments has been known since their early discovery. However, the lack of knowledge of the molecular mechanisms coded in phage genomes hindered the development of the field. With current molecular methods, the last decade has been a resurgence of the field. The Special Issue on “Diversity and Evolution of Phage Genomes” is a great example with its 17 manuscripts published. It covers some of the latest metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The phylogenetic tree based on the complete genomes of BUCT541 and related phages showed that BUCT541 shared the closest evolutionary relationship with the K. pneumoniae phage vB_KpnS_ZX4 (GenBank: NC_054654.1), and also had a close evolutionary relationship with Vibrio phage pYD38-A (GenBank: JF974312.1) and Aeromonas phage pIS4-A (GenBank: NC_042037.1). These results demonstrate the genetic diversity of BUCT541 and provide further information for exploring the genomic evolution of phages (Hatfull and Hendrix, 2011;Reyes and Vives, 2020). ORF 69 of phage BUCT541 was annotated as lysozyme which has a conserved structure and function (Baase et al, 2010).…”
Section: Discussionmentioning
confidence: 64%
“…The phylogenetic tree based on the complete genomes of BUCT541 and related phages showed that BUCT541 shared the closest evolutionary relationship with the K. pneumoniae phage vB_KpnS_ZX4 (GenBank: NC_054654.1), and also had a close evolutionary relationship with Vibrio phage pYD38-A (GenBank: JF974312.1) and Aeromonas phage pIS4-A (GenBank: NC_042037.1). These results demonstrate the genetic diversity of BUCT541 and provide further information for exploring the genomic evolution of phages (Hatfull and Hendrix, 2011;Reyes and Vives, 2020). ORF 69 of phage BUCT541 was annotated as lysozyme which has a conserved structure and function (Baase et al, 2010).…”
Section: Discussionmentioning
confidence: 64%